Discrimination, regulations and the optimal hiring process - Ishac, Richard (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2024)
This article provides a theoretical framework for comparing two different hiring practices: an unpaid competitive internship that is followed by a potential job offer versus a standard series of interviews. After fully characterizing the optimal hiring process, I show that high-ability minorities can be harmed by labour regulations that cause employers to shift towards a hiring process in which they are more likely to discriminate. Furthermore, preventing employers from giving truthful references is shown to exacerbate the obstacles to employment of a community traditionally facing discrimination.